An Intuitive Logical Woman: Personality of Main Female Character in “Arrival” Movie by Eric Heisserer - Brajannoto, Destoprani; Rasyid, Yumna; Lustyantie, Ninuk (Humaniora, 2018)
This research examined the main female character in the movie "Arrival" by Eric Heisserer. The focus of this research was to know the form of personality, desire, the fulfillment of desires, and to find out psychic conflict that is experienced by her by using the theory of Freud and Lacan. The research applied qualitative method by doing steps of using data collection, data analysis, and data presentation. The results show that Dr. Louise Bank has a different woman personality from other women in general, where Id dominates some of the behaviors shown her. Her desire is always followed by an effort in fulfilling; it is shown by Dr. Louise Bank who can use her intuitive, logical mind well to find some ways and solutions in the process of solving it. The most prevalent psychic conflicts in her are the fear and anxiety of new experiences and glance of visions that always keep her in an unpleasant state or condition.